The in vivo study of open fracture in New Zealand white rabbit using orthopaedic metal implant coated with silver composite – A pilot study - Mohd Jan, Nurul Hafiza; Zulkifly, Ahmad Hafiz; Ibrahim, Mohd Zulfadzli; Shaban, Munirah (2017)
INTRODUCTION: Bacterial infection during implant placement is a serious complication. The reason for this infection is mainly due to contamination during surgical implantation with the formation of a resistant biofilm at the implant surface. The infection risks may be overcome by application of orthopaedic metallic implant coated with 3% silver composite as alternative treatment of implant-infection related. The purpose of this study was to investigate the potential effect of test material against infection through in vivo experimental setting.